The Efficacy of High-Dose Dexamethasone vs. Other Treatments for Newly Diagnosed Immune Thrombocytopenia: A Meta-Analysis - Xiao, Qirong; Lin, Bicun; Wang, Hanyu; Zhan, Weiwu; Chen, Ping (Frontiers in Medicine, 2021)
Objective: To compare the therapeutic efficacies of high dose dexamethasone, prednisone and rituximab in combination with dexamethasone for newly diagnosed ITP（Immune Thrombocytopenia, ITP） patients. Methods and results: Relevant publications for this study were obtained by searching PubMed, Embase, Cochrane, and CNKI（National Knowledge Infrastructure，CNKI） databases following the PRISMA guidelines. A total of, 15 publications were retrieved that contained sufficient data from 1362 patients for high quality analysis of this study endpoints. Data analysis was carried out using Stata 11.0 software. The primary outcomes were OR (Overall Response, OR) at 1 month after intervention and SR at 6 months and 12 months. The secondary outcomes were AEs and relapse. There were no differences in the OR, while the SR was higher at 6 months (p=0.001) as well as 12 months (p=0.000) in the rituximab + dexamethasone group. In addition, the incidences of AEs (p=0.008) were also higher in the rituximab + dexamethasone group. Dexamethasone was superior to prednisone based on OR (p=0.006). We found no differences in SR at 6 months between dexamethasone and prednisone but SR at 12 months was higher in the dexamethasone group (p=0.014). The relapse rate was higher in the high dose dexamethasone group compared to the rituximab + dexamethasone group (p=0.042). Conclusion: This demonstrated that new treatment options such as Rituximab + dexamethasone, could be a good alternative to traditional therapy in improving long-term response and reducing the rates of relapse. However, further studies are required on the increased risk of AEs associated with Rituximab + dexamethasone.